2023
DOI: 10.3390/ma16093547
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Decaying Fungi: From Timber Degradation to Sustainable Insulating Biomaterials Production

Abstract: Addressing the impacts of climate change and global warming has become an urgent priority for the planet’s well-being. In recent decades the great potential of fungal-based products with characteristics equal to, or even outperforming, classic petroleum-derived products has been acknowledged. These new materials present the added advantage of having a reduced carbon footprint, less environmental impact and contributing to the shift away from a fossil-based economy. This study focused on the production of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…Commonly, the volumetric swelling of MBCs is directly correlated with the water absorption capability of the material, which leads to changes in volume and dimensions [ 38 ]. Thus, the outcomes of this investigation are consistent with those of a prior study, which indicated that the volumetric swelling of MBC materials ranged between 0.28 and 21% [ 38 , 62 , 64 ].…”
Section: Resultssupporting
confidence: 89%
“…Commonly, the volumetric swelling of MBCs is directly correlated with the water absorption capability of the material, which leads to changes in volume and dimensions [ 38 ]. Thus, the outcomes of this investigation are consistent with those of a prior study, which indicated that the volumetric swelling of MBC materials ranged between 0.28 and 21% [ 38 , 62 , 64 ].…”
Section: Resultssupporting
confidence: 89%
“…This study attributed the increased swelling to the material's heightened ability to absorb water, aligning with several previous research projects [22,29,54]. Importantly, the volumetric swelling of MBCs in this study was within the range reported in earlier studies (0.28 to 21%), with the extent of swelling varying according to the MBCs distinct water absorption capabilities [22,29,55].…”
Section: Water Absorption and Volumetric Swellingsupporting
confidence: 90%
“…This study attributed the increased swelling to the material's heightened ability to absorb water, aligning with several previous research projects [22,29,54]. Importantly, the volumetric swelling of MBCs in this study was within the range reported in earlier studies (0.28 to 21%), with the extent of swelling varying according to the MBCs distinct water absorption capabilities [22,29,55]. The water absorption ability (104.89-244.08%) of the MBCs in this study fell within the ranges reported in previous studies (24.45-560%) when submerged in water over 24-192 h [16,23,24,39,44].…”
Section: Water Absorption and Volumetric Swellingsupporting
confidence: 90%
See 2 more Smart Citations